Measurement of the vascular pedicle width predicts fluid repletion: a cross-sectional comparison with inferior vena cava ultrasound and lung comets. Issue 1 (December 2015) - Salahuddin, Nawal; Hussain, Iqbal; Alsaidi, Hakam; Shaikh, Quratulain; Joseph, Mini; Hawa, Hassan; Maghrabi, Khalid
Abstract Background Determination of a patient's volume status remains challenging. Ultrasound assessments of the inferior vena cava and lung parenchyma have been shown to reflect fluid status when compared to the more traditional static and dynamic methods. Yet, resource-limited intensive care units (ICUs) may still not have access to bedside ultrasound. The vascular pedicle width (VPW) measured on chest radiographs remains underutilized for fluid assessment. In this study, we aimed to determine the correlation between ultrasound assessment and vascular pedicle width and to identify a discriminant value that predicted a fluid replete state. Methods Eighty-four data points of simultaneous VPW and inferior vena cava measurements were collected on mechanically ventilated patients. VPW measurements were compared with lung comet scores, fluid balance, and a composite variable of inferior vena cava diameter greater than or equal to 2 cm and variability less than 15 %. Results A VPW of 64 mm accurately predicted fluid repletion with a positive predictive value equal to 88.5 % and an area under the curve (AUC) of 0.843, 95 % CI 0.75–0.93, p  < 0.001. VPW closely correlated with inferior vena cava diameter (Pearson'sr  = 0.64, p  = <0.001). Poor correlations were observed between VPW and lung comet score, Pearson'sr  = 0.12, p  = 0.26, fluid balance, Pearson'sr  = 0.3, p  = 0.058, and beta natriuretic peptide, Pearson'sr  = 0.12, p  = 0.26. Conclusions This study shows a high predictive ability of the VPW for fluid repletion, as compared to an accepted method of volume assessment. Given the relationship of fluid overload and mortality, these results may assist fluid resuscitation in resource-limited intensive care units.